The optimum sawing pattern for oil palm stems - Bakar, Edi Suhaimi; Febrianto, Fauzi; Ashaari, Zaidon (2005)
The shortage in wood supply makes the effort to find alternative wood material become more and more important. It was reported that the outer parts of oil palm stems could be used as solid wood after being properly treated, and oil palm stems were one of strategic solid wood alternative in Malaysia. Being a monocotyledon, oil palm stems have a contradictory characteristic to the conventional hardwoods and softwoods and thus the sawing patterns suitable for hardwoods and softwoods should not be suitable for the oil palm stems. Two modified sawing patterns (“polygon sawing”, PS and “cobweb sawing” CS) and one ordinary sawing pattern (life sawing, LS) were compared. The purpose of this study was to find the most suitable sawing pattern for oil palm stems in term of the outer lumber recovery and quality, and the sawing time. The CS provided the highest outer lumber recovery (35%) followed by PS (27%) and LS (23%). The PS provided the highest occurrence of wide lumbers, followed by the CS and LS. The CS needed more than twice effective sawing time (15.4 min.) than the LS and PS. It was concluded that the PS was to be the most suitable pattern for the sawing of oil palm stem.